Socio-economic disparities in heart disease in the Republic of Lebanon: findings from a population-based study. Issue 1 (29th July 2010) - Ramahi, Tarik; Khawaja, Marwan; Abu-Rmeileh, Niveen; Abdulrahim, Sawsan
Abstract : Background: Socio-economic inequalities in the incidence of heart disease exist in developed countries. No data are available on the relation between heart disease and socio-economic status in Arab countries. This study examined the relation between heart disease and socio-economic status (income and education) among adults in Lebanon. Methods: The study examined data from 7879 respondents aged 40 years or more in the 2004 Lebanese Survey of Family Health. The dependent variable was reported heart disease. The main independent variables were education and household income. The analysis adjusted for the classic risk factors of coronary heart disease (CHD), namely smoking, diabetes mellitus, hypertension, hypercholesterolaemia, age, sex and other socio-demographic variables. Bivariate associations were calculated using χ 2 tests. Adjusted ORs for heart disease were calculated using multivariate logistic regression models. Results: 7.5% of respondents reported cardiac disease, 15.2% hypertension, 10.1% diabetes, 3.2% hypercholesterolaemia and 47.5% smoked at the time or previously. After adjustment for the classic risk factors of CHD, reported heart disease was inversely associated with education (OR=1.53, 95% CI 1.15 to 2.04, for those with less than elementary and OR=1.34, 95% CI 1.00 to 1.80, for those with elementary education). Reported heart disease was also inversely associated with income (OR=1.40, 95% CI 1.09 to 1.80, for those in the lowest income bracket). Past smoking, hypertension, age, male sex, marriage and residence in Beirut were all significantly associated with reported cardiac disease. Conclusions: In Lebanon, adults with lower income and educational levels had a higher prevalence of heart disease independent of the risk factors of CHD.